Genetic diversity of populations of Simulium reptans s.l. (Diptera: Simuliidae) in the territory of Russia and Northern Kazakhstan - Vaulin, Oleg V.; Petrozhitskaya, Liudmila V.; Novgorodova, Tatiana A. (Zootaxa, 2024)
The presence of sibling (cryptic) species among bloodsucking black flies can be a serious problem in assessing both their diversity and the role of individual species in the transmission of dangerous human and animal pathogens. The peculiarities of molecular genetic structure of populations and ecology of black flies of Simulium reptans s.l. (complex of Simulium reptans (Linnaeus) and Simulium reptantoides Carlsson) in European and Asian parts of Russia and Northern Kazakhstan in comparison with populations from Central and Northern Europe were investigated. Using restriction analysis of the COI gene and subsequent sequencing, we searched for unique mtDNA variants that could belong to previously undescribed forms of the studied group. In the north of the European part of Russia (north of Eastern Europe), only S. reptans A was registered, and in the Asian part of Russia (Siberia) and Northern Kazakhstan, only S. reptans B was found. Using phylogenetic analysis of the total data, three branches of S. reptans B were revealed and named in accordance with the areas of their distribution–East European, Eurasian and Asian. Simulium reptantoides Carlsson has currently been found only in Europe. The peculiarities of distribution and possible adaptations to different habitats of S. reptantoides and representatives of individual groups within S. reptans are discussed. Based on the characteristics of the sampling sites of the studied specimens, as well as the samples available in the NCBI database, the ecological and geographical features of the habitats of the molecular forms of Simulium reptans A and B were revealed. To obtain more accurate information on the distribution of S. reptans A and B forms in Eurasia, taking into account the elevational zonation, it is necessary to conduct additional studies in the mountainous regions of South-Western Europe, Siberia and Northern China. Based on the sequences presented in the DNA database, a method (AS-PCR COI variant) for separating the cryptic species–Simulium reptans (Linnaeus) and S. reptantoides Carlsson–was proposed. During testing of this method on the material collected in Russia and Northern Kazakhstan, only S. reptans was identified (S. reptantoides was absent), which completely coincided with the sequencing results. To further confirm the effectiveness of the method, it is necessary to conduct testing on material including representatives of the both species.